Mode confusion of human–machine interfaces for automated vehicles. Issue 5 (31st August 2022) - Eom, Hwisoo; Lee, Sang Hun
Abstract: In this study, we designed two user interfaces for automated vehicles operated in the modes that correspond to the Society of Automotive Engineers automation levels 0–3. The first is a level-centred interface that allows the driver to increase or decrease the automation level step-by-step. The second is a function-centred interface that has independent driving controls in the longitudinal and lateral directions. We implemented prototypes for the two interfaces and conducted driver-in-the-loop experiments on a driving simulator to verify their effectiveness in the driver's mode awareness. For events on the road, the participants took actions to control the vehicle, which might cause mode changes, and answered the modes he/she believed. The experimental results show that the mode confusion rate of the level-centred interface is twice higher than that of the function-centred interface. Also, visual feedbacks can reduce the mode confusion rate dramatically. The results show that a function-centred user interface combined with adequate visual and/or auditory feedback is essential to improve driver's mode awareness when driving an automated vehicle. Graphical Abstract: